Pencatatan Manual Pada Laporan Keuangan Ayumi Salon di Era Digital - Asep Mulyana; Mariam M; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Ayumi salon is one of the SMEs engaged in hairdressing services. Ayumi salon has been operating for about 34 years and was founded by Mrs. Hj Tati in 1989 which is located on Jl turi timur Rt/rw 002/001, Tanjung Jaya Village, Tempuran, Karawang. The aim is to find out the financial recording reports at Ayumi salons that apply manual methods in the digital era. The method used in this visit was descriptive and observative. The method used in this study was descriptive and observative. Data collection used interviews, observation, documentation, and literature. Financial statements are things that affect a company's income. Financial reports at Ayumi salon still use a manual system, namely by recording manual bookkeeping every day. this is due to the high costs incurred, as well as the lack of human resources capable of operating the system. manual financial reports have advantages and disadvantages that will have an impact on the business that is being carried out, therefore UMKM Ayumi salon studies accounting in the digital era to help compile financial reports.Â